Expressão das proteínas CHK2, γH2AX e TP53 em carcinoma de células escamosas de boca de indivíduos fumantes e não fumantes - Lauren Frenzel Schuch (2019)
Oral cancer accounts for about 4% of neoplastic diseases, and squamous cell carcinoma is the most common type, accounting for about 90 to 95% of cases. Cigarette smoking is the main etiological factor for oral cancer, causing DNA damage and mutations that, if not repaired, lead to lesions. Cigarette-associated DNA damage has been studied in different cancers, but is still poorly explored in relation to oral cancer. Checkpoint kinase 2 (CHK2) and P53 are proteins that are involved in the cell cycle checking process and are responsible for repairing DNA damage. The H2AX protein is a nuclear histone that undergoes phosphorylation in response to DNA damage, especially double strand breaks. The aim of this study was to assess the DNA damage response through the expression of checkpoint kinase 2 (CHK2), γH2A histone family member X (γH2AX) and TP53 among smokers and non-smokers with oral squamous cell carcinoma (OSCC). In addition, associations amongst immunoexpression of studied proteins, clinicopathologic data and histopathological grading were analyzed. Thirty-five individuals (18 nonsmokers and 17 smokers) with OSCC of the tongue and/or floor of the mouth were included. Immunohistochemistry was carried out for γH2AX for identification of double-strand breaks, CHK2 and P53 for evaluation of the induction of cell cycle arrest. Descriptive and statistical analyses were performed. The survey consisted of 22 males (62.8%) and 13 females (37.2%), with a mean age of 63.9 years. Fifty percent of non-smokers OSCC were well-differentiated tumors, whereas for smokers, OSCC were moderately differentiated and poorly differentiate tumors, equally (35.3% each). Overall, 31 (88.6%) cases were CHK2-positive, 27 (77.2%) were γH2AX-positive and 23 (65.7%) were TP53-positive. No association among these proteins with smoking and non-smoking habits was observed (p>0.05). Similarities in the CHK2, γH2AX and P53 immunohistochemical staining pattern were observed between smokers and non-smokers with OSCC in this survey, and the immunoexpression was not associated with clinicopathologic parameters. Overall, the results indicated consistent expression of these proteins in OSCC. This study provides information about the DNA damage in oral carcinogenesis.